A STUDY ON THE PHENOMENA IN LESU-LULI`S POETRY IN BOBONARO MUNICIPALITY - Agostinho dos Santos Gonçalves; Anna Isabela Sanam; Paulina Dau De Jesus Soares (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
lesu - luli The aim of this research was to describe the history of Lesu-luli and to find the intrinsic elements in Lesu-luli’s Poetry. This research was a phenomenological research that using the descriptive method. In this study, the primary data was the script of lesu – luli’s poetry while the secondary data was the source text, such as literary theory books, the results of another literature research about poetry and culture, as well as the source from the internet. In this study, there were four informants. The data gathering from the informants was analyzed in three steps, namely data reduction and translating, data presentation and conclusion or verification. Based on the result of this study the history of “lesu-luli”  is coming from the name of two grandfathers namely Mau Lesu and Lesu Tali. Mau Lesu came from uma Slelo while Lesu Tali came from uma Bere Ubu. Both of the grandfathers were a captain and a major. They had played the important role to struggle and liberate for the tradition of lesu luli. This struggle involved the eight households (that now become the eight of uma lisan or uma lulik) and also the kings. The kings were two peoples namely Talentuand Kornel. Talentu came from uma Bero Mau while Kornel came from uma Kali Ubu. Lesu – luli not only a sacred stone without meaning. Peoples in Meligo village made this place as a place where the people could ask the blessing of the ancestors and God. This was a culture and tradition that regularly conducted every year around September or October. Peoples in Meligo village believed that if the ceremony of lesu – luli was not celebrated, it would cause died, disaster, bad seeds, and drought (dry season). The intrinsic elements found in lesu – luli’s poetry were: (1) Structure. In the structural analysis, the writer found two elements line and stanza. The types of the stanza in lesu – luli’s poetry were a triplet, the quatrain, and the cinquain/quintet stanza. (2) Sound. The most type of sound found in lesu – luli’s poetry was ended rhyme sound. (3) Figurative language or diction. The style of language or diction that found in lesu – luli’s poetry was a formal language and the selection of words in this poem was very religious. Finally, the writer conclude that a culture must be protected because a culture is a foundation of human life.